Perceived effective and feasible strategies to promote healthy eating in young children: focus groups with parents, family child care providers and daycare assistants. (December 2016) - Vandeweghe, Laura; Moens, Ellen; Braet, Caroline; Van Lippevelde, Wendy; Vervoort, Leentje; Verbeken, Sandra
Abstract Background The aim of the current study is to identify strategies to promote healthy eating in young children that can be applied by caregivers, based on their own perceptions of effectiveness and feasibility. Whereas previous research mainly focused on parental influences on children's eating behavior, the growing role of other caregivers in the upbringing of children can no longer be denied. Methods Four focus groups were conducted with three types of caregivers of post-weaning children under 6 years old: parents (n  = 14), family child care providers (n  = 9), and daycare assistants (n  = 10). The audiotaped focus group discussions were transcribed and imported into Nvivo 10.0 for thematic analysis. The behaviors put forward by the caregivers were categorized within three broad dimensions: global influences, general behaviors, and specific feeding practices. Results Perceived effective strategies to promote healthy eating behavior in children included rewards, verbal encouragement, a taste-rule, sensory sensations, involvement, variation, modeling, repeated exposure, and a peaceful atmosphere. Participants mainly disagreed on the perceived feasibility of each strategy, which largely depended on the characteristics of the caregiving setting (e.g. infrastructure, policy). Conclusions Based on former research and the current results, an intervention to promote healthy eating behaviors in young children should be adapted to the caregiving setting or focus on specific feeding practices, since these involve simple behaviors that are not hindered by the limitations of the caregiving setting. Due to various misconceptions regarding health-promoting strategies, clear instructions about when and how to use these strategies are necessary.